PRESCRIBING TREND AMONG HOSPITALIZED PEDIATRIC PATIENTS IN PRIVATE SECTOR HOSPITAL: A PROSPECTIVE OBSERVATIONAL STUDY IN NADIAD, INDIA - B PATEL, SANDIP; P PATEL, YASH; B SHAH, SHISHAV (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Purpose of this study was to analyze the prescription pattern among the hospitalized pediatric patients in private sector hospital. Methods: The study was conducted from January 2018 to April, 2018 at Shaishav Hospital, Nadiad, Gujarat, India, and 178 patients were included into the study. Results were obtained by applying the World Health Organization (WHO) prescribing indicators as well as Indian Academy of Pediatrics List of Essential Medicines (IAP-LEM). Results: During the study period, infectious disease such as pneumonitis, bronchitis, enteric fever, gastroenteritis, and dehydration were the dominant disease among the patients. Average number of drugs per prescription was four but in many of prescription, poly-pharmacy has shown. Antibiotic agents were the most prescribed drug (38.6%) among different classes of drugs. Use of the parenteral route of drug administration was used beyond the range stated by the WHO (59% prescriptions vs. 13–24% WHO range). We found that doctor followed IAP-LEM (in 99.78% cases) for prescribing as well as for dosing also, which was very impressive. Conclusions: As this study indicates, there is a need of development of evidence-based treatment protocols for common disease condition for the rational use of medication, especially for an antibiotic medication.